Treatment of recurrent tracheal adenoid cystic carcinoma with a covered airway stent loaded with Iodine-125 seeds: a 5-year follow-up case report - Yang, Zhen; Wang, Yafei; Li, Zhenhua; Geng, Shuang; Hu, Yi (Frontiers in Oncology, 2024)
BackgroundThe treatment of recurrent tracheal adenoid cystic carcinoma (TACC), a rare pulmonary malignant tumor, typically involves bronchoscopic interventional therapy for patients ineligible for surgery or external radiotherapy. This report describes an innovative treatment approach for TACC, initially managed with interventional bronchoscopy and subsequently with a Y-shaped airway stent loaded with 125I seeds, following recurrence after 2 years.Case presentationA 50-year-old man presented with intermittent coughing for 2 months and was admitted to the hospital after the discovery of TACC a month earlier. Preoperative bronchial artery embolization was performed to reduce the risk of bleeding, followed by bronchoscopic tumor resection in January 2017 using an electric loop at the base, complemented by argon plasma coagulation (APC) and cryotherapy. Although short-term outcomes were favorable, the long-term prognosis remained suboptimal. Due to tumor recurrence, airway tumor resection and implantation of the 125I seed stent were performed under bronchoscope guidance in early 2019. The stent was removed 5 months later. The patient tolerated the procedure well and exhibited no signs of relapse or progression during the 5-year postoperative follow-up period. This case illustrates the successful application of a stent loaded with 125I seeds for treating unresectable TACC.ConclusionsTreatment of TACC with a covered airway stent loaded with 125I seeds may be a safe, effective, and scalable method.